Alternative Dispute Resolution Systems in the Zimbabwean media industry and the debate on self-regulation - Mhiripiri, N. A. (Intellect, 2021)
Alternative Dispute Resolution Systems (ADRs) for conflict resolution in the media are processes ‘alternative’ to statutory courts. Players in the Zimbabwean media industry are developing and promoting ADRs as a means of evading the restrictive, expensive and time-consuming legal courts. Media and complainants arguably have speedier and satisfying resolutions outside the courts. However, typical of Zimbabwe there are marked signs of contestation, controversy and lack of unanimity with regard to the ADRs. On the one hand, there is the Voluntary Media Council of Zimbabwe (VMCZ), a self-regulatory structure favoured by the privately owned media players. On the other hand, there is the Zimbabwe Media Commission (ZMC) formed under statutory law and whose structure is still not adequate to resolve cases brought before it. VMCZ and ZMC are contesting for legitimacy and in various ways they present dialectical positions on the debate on self-regulation. One media house, Alpha Media Holdings, has formed its own ADR system that uses the ombudsman. This article uses press reports and interviews of key people in the media and the ADRs in order to ascertain the effectiveness and problems of the evolving processes, making comparisons with the United Kingdom and South African scenarios where similar debates on Press Councils are topical, especially after the publication of the report on the Leveson Enquiry.